Spectrally Multiplexed Quantitative Lateral Flow Immunoassay for Bordetella Pertussis Antibodies - Merenheimo, Heli (My University, 2026)
Pertussis, caused by Bordetella pertussis, remains a significant public health concern despite high vaccination coverage. Diagnosis based on serology typically relies on the detection of antibodies against pertussis toxin (PT), which is uniquely produced by Bordetella pertussis. However, PT is also included in all acellular pertussis vaccines, complicating the differentiation between infection and vaccine-induced immune responses. Conventional serological methods such as enzyme-linked immunosorbent assays require centralized laboratories and long turnaround times, limiting their suitability for rapid diagnostics and large-scale surveillance. The aim of this study was to conduct proof of concept for a spectrally multiplexed, quantitative lateral flow immunoassay for the simultaneous detection of anti-PT IgG and IgA antibodies. The assay employs upconverting nanoparticles as fluorescent reporters, enabling detection of multiple antibody isotypes from a single test line using a shared near-infrared excitation source and spectrally distinct visible emissions. Assay performance was evaluated using WHO international reference standards and a clinical serum sample panel (n = 30). Spectral multiplexing was successfully achieved with minimal spectral overlap between UCNP reporters. In singleplex format, the limits of detection were 2.6 IU/mL for anti-PT IgG and 1.0 IU/mL for anti-PT IgA, while in multiplex mode the IgG LoD remained unchanged and the IgA LoD increased to 5.0 IU/mL. The multiplex assay showed an average coefficient of variation of 24.4%. Anti-PT IgG quantification demonstrated strong correlation with a reference antiserum (R² = 0.987), whereas correlation with clinical serum samples was lower (R² = 0.637). Anti-PT IgA detection was technically feasible but exhibited higher variability and reduced linearity in serum-containing samples. These results demonstrate the feasibility of UCNP-based spectral multiplexing in a lateral flow format for pertussis serology. While further optimization and clinical validation are required, the developed assay provides a promising foundation for quantitative, multiplexed point-of-care diagnostics and may support improved serological interpretation of pertussis infection and immunity.
Keywords: multi-analyte; POCT; NPT